Maternal Mirtazapine Selectively Enhances Hippocampal LTP without Reversing Stress-Associated Alterations in Basal Transmission, Short-Term Plasticity, or Open Field Behaviour in Rat Offspring - Gasparova, Zdenka; Bukatova, Stanislava; Dubovicky, Michal (Drug Research, 2025)
Maternal stress during pregnancy has profound effects on offspring, disrupting brain development and behaviour. Mirtazapine, an antidepressant commonly prescribed for maternal depression, has an unclear impact on offspring neurophysiology and behaviour. We hypothesized that maternal mirtazapine treatment during pregnancy and lactation would influence locomotor activity, exploratory behaviour, and hippocampal synaptic plasticity in rat offspring, particularly in the context pre-gestational stress.Offspring from control or chronically stressed dams, treated with either vehicle or mirtazapine, were assessed. Behavioural responses were evaluated using the open field test, and the hippocampus was examined electrophysiologically to measure population spike (PS) amplitude of compound action potential, field excitatory postsynaptic potential (fEPSP) slope, short-term plasticity, and long-term potentiation (LTP).Maternal stress significantly reduced exploration of the central zone, indicating increased anxiety-like behaviour, although post hoc comparisons did not reach significance. Mirtazapine treatment did not reverse these behavioural alterations. PS amplitude was unaffected across groups, but fEPSP slope was significantly reduced in stressed offspring, with no recovery observed following mirtazapine treatment. Paired-pulse ratios across inter-pulse intervals (10–100 ms) were consistently decreased in the stressed group, indicating impaired short-term synaptic plasticity, which mirtazapine did not restore. In contrast, LTP showed a significant stress×treatment interaction (p=0.0201), suggesting that mirtazapine selectively enhanced long-term plasticity in stressed offspring.Mirtazapine did not reverse behavioural impairments or basal synaptic transmission deficits induced by maternal stress. It may selectively enhance long-term synaptic plasticity, suggesting its potential to modulate specific neurodevelopmental outcomes following prenatal stress exposure.
Keywords: antidepressant drugs; anxiolytic drugs; behavioural pharmacology; psychiatric disorders; drug research